2011
DOI: 10.2337/dc11-1012
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Unstable Mutation in Mitochondrial DNA Responsible for Maternally Inherited Diabetes and Deafness

Abstract: OBJECTIVEThe m.3243A>G mutation in mitochondrial DNA (mtDNA) is responsible for maternally inherited diabetes and deafness (MIDD). Other mtDNA mutations are extremely rare.RESEARCH DESIGN AND METHODSWe studied a patient presenting with diabetes and deafness who does not carry the m.3243A>G mutation.RESULTSWe identified a deficiency of respiratory chain complex I in the patient’s fibroblasts. mtDNA sequencing revealed a novel mutation that corresponds to an insertion of one or two cytosine residues in the codin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 14 publications
(18 reference statements)
0
6
0
Order By: Relevance
“…The results showed that no pathogenic mutations were found in the non-coding region of WFS1 gene of the patient and his families (Table 3 ). In addition, we screened mitochondrial mutations of m.3337G > A and m.3243A > G, which were associated with WS and maternally inherited diabetes and deafness (MIDD), respectively [ 15 , 16 ]. Both mutations were not found in the patient and his families (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that no pathogenic mutations were found in the non-coding region of WFS1 gene of the patient and his families (Table 3 ). In addition, we screened mitochondrial mutations of m.3337G > A and m.3243A > G, which were associated with WS and maternally inherited diabetes and deafness (MIDD), respectively [ 15 , 16 ]. Both mutations were not found in the patient and his families (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, the phenotype of a pathogenic mtDNA mutation, or the severity of an mtDNA mutation that may not be pathological in some cases, could be influenced by the mitochondrial DNA haplogroup [38] . In addition, the genetic instability of mtDNA heteroplasmic mutations in the patient's somatic tissues [39] , or the nuclear background, by nuclear modifiers, may also play a role in determining mtDNA mutation pathogenicity [40] .…”
Section: Discussionmentioning
confidence: 99%
“…In many (but not all, Noll et al, 1990) cell types, the bulk of ATP is produced by OXPHOS in mitochondria. Since mtDNA encodes components for four out of five mitochondrial respiratory complexes, it is not surprising that mutations in mtDNA have been associated with various human pathologies, such as mitochondrial diseases (Schapira, 2012; Ylikallio & Suomalainen, 2012; Zheng et al, 2012), diabetes (Bannwarth et al, 2011; Maassen et al, 2005; Supale et al, 2012), cancer (Wallace, 2012; Yu, 2012), neurodegenerative disorders (Milone, 2012), and many others. Therefore, understanding cellular mechanisms for the maintenance of mtDNA integrity is of utmost importance as it can provide targets for clinical interventions aimed at the prevention and treatment of human diseases.…”
Section: Introductionmentioning
confidence: 99%